Effects of yoga exercise in reducing the risk of knee osteoarthritis and fibulin-3 levels among overweight population: a randomized controlled trial - Wahyuni, Nila; Adiatmika, I Putu Gede; Vittala, Govinda; Nova Mahendra, Agung (Universitas Udayana, 2023)
Background and purpose: One of the main risk factors for knee osteoarthritis is overweight. The purpose of this study is to determine the effectiveness of yoga exercise in reducing the risk of knee osteoarthritis and fibulin-3 levels in overweight populations. Methods: This study was a randomized controlled trial involving 24 participants who met the inclusion and exclusion criteria. Participants were randomly divided into two groups: group one was given yoga exercise intervention and group two was given neuromuscular coordination exercise as the control group. Risk of knee osteoarthritis measurements were carried out using The Western Ontario and McMasters University Osteoarthritis Index (WOMAC). Fibulin-3 measurement used ELISA technique using human fibulin-3 kit, FBLN3 BT-LABkit 96T E4667Hu. Results: Participants of both groups were comparable, except for age where the control group is slightly older. Pre and post-test comparison showed improvement in pain, stiffness, physical function, total WOMAC score, and fibulin-3 levels in both groups. While, the post-test comparison between the two groups showed that yoga group has better scores on all indicators compared to the control groups which was statistically significant (p≤0.001). Conclusion: Both interventions are effective in reducing the risk of knee osteoarthritis and fibulin-3 levels, but yoga showed better result. We recommend yoga training to reduce the risk of knee osteoarthritis compared to conventional training. Future research is needed to measure other knee osteoarthritis biomarkers that describe the pathological process of knee osteoarthritis.